2(m-4)+5=9

Simple and best practice solution for 2(m-4)+5=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-4)+5=9 equation:


Simplifying
2(m + -4) + 5 = 9

Reorder the terms:
2(-4 + m) + 5 = 9
(-4 * 2 + m * 2) + 5 = 9
(-8 + 2m) + 5 = 9

Reorder the terms:
-8 + 5 + 2m = 9

Combine like terms: -8 + 5 = -3
-3 + 2m = 9

Solving
-3 + 2m = 9

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2m = 9 + 3

Combine like terms: -3 + 3 = 0
0 + 2m = 9 + 3
2m = 9 + 3

Combine like terms: 9 + 3 = 12
2m = 12

Divide each side by '2'.
m = 6

Simplifying
m = 6

See similar equations:

| 17y+3=-25 | | 52-(3x-4)=x | | 2x+14+2x-7=55 | | 6a+9b=-7 | | 65-(2x+5)=3x | | -4+8x=-4(1+8x) | | -9=-8+r/16 | | 14-5m=5-8m | | 3x-34=12x-74 | | 90=4x-(2x-14) | | 3x-(x+26)=180 | | 5y-10=40 | | 4w-8w=28 | | 2x+(x-33)=90 | | -4=7x+1-8 | | 4(x-5)=x+4 | | 11n=10+16 | | 4x+(x+35)=90 | | (3x/(x-7))-((x+7)/x)=0 | | (3x/(x-7))-((x+7)/x) | | x-3=(5x-1)^1/2 | | 7g=6 | | 700-2x=50+2x | | -49.95-20x= | | x^2+4x-y=7 | | V=x(14-2x)(10-2x) | | 5(2x-7)=3(4x+9) | | 2x/5=x+6 | | 7m-3=3m+17 | | 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 |

Equations solver categories